Analysis of the pigments in two modern Egyptian papyri using XRF technique - Raysa Costa Nardes (Brazilian Journal of Radiation Sciences, 2021)
In this work, two modern Egyptian papyrus belonging to a private collection were analyzed using X-Ray Fluorescence technique (XRF). The papyri are genuine, made from the papyrus plant, and hand-painted. The papyri were bought in the city of Cairo, Egypt, in the ‘80s and brought to Brazil in the same period. XRF analyses were performed using a portable spectrometer ARTTAX (X-ray tube with Mo anode and a Silicon Drift Detector XFlash®, Bruker AXS Inc.). XRF measurements were carried out under the following experimental conditions: 35 kV, 600 μA, unfiltered x-ray beam, air atmosphere, acquisition time of 600 s. The elements detected in the two papyri were: Si, Al, S, Cl, K, Ca, Ti, Cr, Mn, Fe, Ni, Cu, Zn, Sr, Ba and Pb. Through the XRF analysis it was possible to evaluate the pigments found in the two papyri are different from each other. In the analysis of the blue color, present in the papyrus, it was observed that the composition of this color can be a mixture of two pigments: Egyptian blue (CaCuSi₄O₁₀) and Lithopone (ZnSBaSO4). Most of the pigments on the papyri were thus recognized to be modern, their syntheses, or refinement processes not being known to ancient Egyptians.